Development and Validation of an Instrument to Enhance the Community Pharmacy Practitioner's Knowledge towards Handling of High Risk/ Alert Medications (Global Journal of Medical Research, 2019)
Abstract not found
Keywords: high risk medications; community pharmacists; learning modules; content and face validation; reliability.